Uji Efektivitas Ekstrak Daun Sirih Hijau (Piper betle L.) untuk Menghambat Pertumbuhan Jamur Geotrichum sp. Penyebab Penyakit Busuk Asam pada Buah Tomat - Mahdalena, Irma; Suprapta, Dewa Ngurah; Sudarma, I Made (Agrotrop : Journal on Agriculture Science, 2025)
Effectiveness of Green Betel Leaf Extract ( Piper betle L.) to Inhibit the Growth of Geotrichum sp. the Cause of Sour Rot Disease in Tomato Fruit. Sour rot disease is one of the important diseases on tomato fruit caused by the fungus Geotrichum sp. Environmentally friendly control method of the disease can be done by using botanical fungicide. Green betel leaf ( Piper b etle L.) is one of the plants that can be used as an botanical fungicide. This study aims to determine the effectiveness of green betel leaf extract ( P. b etle      L.) to inhibit the growth of the fungus Geotrichum sp. causing sour rot disease in tomato fruits. Inhibition test of green betel leaf extract was done with colony method using extract concentrations of  0.08%, 0.16%, 0.32%, 0.40%, 0.48%, 0.56%, 0.64% and control. Effectiveness test of green betel  leaf extract against Geotrichum sp. in vivo on tomato fruit was done using concentrations of 0.5%, 0.75%, 1%, 1.25%, 1.5% and control. The results in vitro test showed that green betel leaf extract at a concentration of 0.48% significantly (p<0.05) suppressed the growth of Geotrichum sp. colony on PDA medium with inhibitory activity by 100%. The result of i n vivo test showed that the treatment with green betel leaf extract at concentration 1.5% significantly (p<0.05) reduced the sour rot disease on tomato fruit caused by Geotrichum sp. This treatment  reduced the sour rot disease on tomato fruit by 64.70%.